2021
DOI: 10.1101/2021.06.02.446106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteome and functional decline as platelets age in the circulation

Abstract: Anucleate platelets circulate in the blood of healthy individuals for approximately 7-10 days during which time their protein composition may change. We hypothesized such changes would be linked to altered structure and function. Here, we separated platelets of different ages based on mRNA content and characterised them using proteomics, immunofluorescence and functional assays. Total protein content was 45±5% (n=4) lower in old platelets compared to young platelets. Predictive proteomic pathway analysis ident… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…16 Interestingly, a recent proteomic study provided the first insights on RPs proteome: it was found that platelet aging leads to a relevant reduction in cytoskeletal protein, a reduction in mitochondria number, lower calcium dynamics and granule secretion, and it has been suggested that old platelets have blunted hemostatic responses and accumulate circulating proteins. 54 Other preclinical studies concerning RPs' biology are summarized in Figure 1 and Table 1. 49,[55][56][57]…”
Section: Insights On Rps Biologymentioning
confidence: 99%
“…16 Interestingly, a recent proteomic study provided the first insights on RPs proteome: it was found that platelet aging leads to a relevant reduction in cytoskeletal protein, a reduction in mitochondria number, lower calcium dynamics and granule secretion, and it has been suggested that old platelets have blunted hemostatic responses and accumulate circulating proteins. 54 Other preclinical studies concerning RPs' biology are summarized in Figure 1 and Table 1. 49,[55][56][57]…”
Section: Insights On Rps Biologymentioning
confidence: 99%